A Theoretical Study about Three Organic Semiconductor Based on Oligothiophenes (Journal of Atomic and Molecular Sciences, 2022)
Three derivatives based on oligothiophenes were theoretically investigatedabout the electronic and charge transport properties using density functional (DFT)theory based on the Marcus-Hush theory. The predicted highest hole mobility is 0.218 $cm^2V^{-1}s^{-1},$ and the highest electron mobility is 0.373 at 300 K. The calculated datademonstrated that the compound 1 should be a high-performance $n$-type organic materialcandidate and compound 3 may well be potential p-type materials with highmobility values. Our work also indicates that the face-to-face $π$-$π$ interaction and $S$-$S$ interactions is favorable for the molecular stacking and charge transport behaviors.The calculated results provide an additional possibility to be able to improve the originsemiconductor performance and design new electronic devices.
Keywords: Organic semiconductor; charge transport; Oligothiophene.